La hantise du précédent en photographie. Généalogies médiumniques et formes de revenances dans la photographie industrielle - Pierre LANNOY (Conserveries Mémorielles)
To give an artistic dimension to his photographs, the photographer needs to build and hold a personal look at the world. But if he is put in the situation to shoot at places already pictured as photographic scenes by significant others, he will eventually be haunted by the presence of these predecessors. A ghost appears between him and the scene, affecting his photographic gaze : the absent photographer influences his current work. In this paper, I try to demonstrate the effectiveness of the haunting precedent in photography, taken as the influence of a style and a work already embodied on a following work. The successor will be shown as stressed by the challenge of simultaneously pointing to and keeping away the forerunner’s presence in his pictures. By doing this, the latecomer tells us a descent story in which he shows himself as holding the role of an imitator, an heir, an innovator, or a revolutionary. Such a genealogy is made apparent within the photographic medium itself, through which relations to dead or living predecessors are exposed. The materials I rely on in this study consist of photographic series that some renowned photographers (Doisneau, Charbonnier, Wolff, Tritschler, Keetman, Sheeler, Evans, Frank) devoted to several car factories. On this basis, the paper suggests that the haunting precedent is a situation with a dynamical structure, that states of mind are pragmatic frames to be handled with, and that references to predecessors appear in a few of typical forms. The main epistemological challenges raised by the method used are also considered.